“Classical Blalock–Taussig shunt” gone wrong: Confusing the right common carotid with right subclavian artery - Idhrees, A Mohammed (Ann Pediatr Cardiol, 2015)
A 14-year-old girl underwent classical Blalock–Taussig shunt at 5 months of age. Computed tomography evaluation showed “Adachi type H” pattern of aortic arch vessels with the right common carotid artery being anastomosed to the right pulmonary artery mistaking it for the right subclavian artery.